Fruit processing and the physiological quality of Euterpe edulis Martius seeds - Cursi,Patrícia Ribeiro (2014)
Different pulping methods were analyzed for Euterpe edulis, with regard to its seed physiological quality, and the physiological performance of seeds submitted to continuous drying and monitored by radiographs was assessed. In order to do so, 2x2 factorial design treatments were carried out, using two different manners to store fruit prior to pulping, immersed in water and not. Also, two different methods for the pulping of fruit were used for each lot; namely, manual and mechanical. Seeds from fruit that had been immersed in water at 40 ºC for 20 minutes showed greater physiological performance than those that had not been immersed in water previously. Immersion in water at 55 ºC resulted in seed death. The pulp extraction method, whether manual or mechanical, did not affect seed physiological performance. Radiographs made it possible to observe that the volume occupied by embryos in the embryo cavity reduced with decreased water content. Mechanical pulping showed no reduction in percentage of seedling emergence for water content up to 33.3%. However, reduction in water content to 16.1% caused seed death. The drying of manually pulped seeds until reaching 39.0% water content did not adversely affect seedling emergence, whereas lower water contents than 25.6% caused seed death.